BACTERIAL VAGINITIS AND VAGINOSIS: CLINICAL, DIAGNOSTIC, AND THERAPEUTIC ASPECTS - Vieira, Alana Beatriz Bueno; Figueiredo, Lara Rufato; Duran, Luana Vieira; Bucci, Valentina Helena Occhialini; Sobiesiak, Roberta Wisch; Gutierrez, Jane Helen da Silva Soares; Vecchia, Beatriz Kaminski Dalla; de Paiva, Maria Letícia Teixeira; Jonck, Gabriela Carvalho; Vieira, Marina Galinari; de Carvalho, Sophia Guimarães Barreto; Manzotti, Jácomo (Seven Editora, 2026)
Vaginitis and bacterial vaginosis are common gynecological conditions and account for a significant proportion of consultations in healthcare services, with substantial impact on women’s quality of life. The main etiologies include bacterial vaginosis, vulvovaginal candidiasis, and trichomoniasis, which differ in terms of epidemiology, pathophysiology, clinical presentation, diagnosis, and treatment. Bacterial vaginosis is the most common cause of vaginal discharge and is characterized by vaginal microbiota dysbiosis and reduction of Lactobacillus species. Vulvovaginal candidiasis results from the excessive proliferation of fungi of the genus Candida, especially Candida albicans. Trichomoniasis, in turn, is a sexually transmitted infection caused by the protozoan Trichomonas vaginalis, associated with a more intense inflammatory response and increased risk of coinfections. Diagnosis is based on clinical evaluation, gynecological examination, and laboratory tests, including vaginal pH analysis, microscopy, and molecular testing when available. Treatment varies according to etiology, with antibiotics used for bacterial vaginosis, antifungals for candidiasis, and antiparasitic agents for trichomoniasis. Accurate identification of these conditions is essential to prevent recurrence, reduce complications, and improve patients’ quality of life. This chapter provides a comprehensive review of the clinical, diagnostic, and therapeutic aspects of vaginitis and bacterial vaginosis, with a comparative focus on the main etiologies.